2021
DOI: 10.3390/jrfm14090428
|View full text |Cite
|
Sign up to set email alerts
|

Industry, Firm, and Country Level Dynamics of Capital Structure: A Case of Pakistani Firms

Abstract: The capital structure appears to be one of the most researched and the most controversial areas in modern corporate finance. Prior literature on determinants of capital structure has concentrated on firm and country level factors by employing static modeling. Static modeling has certain limitations, which do not allow companies to establish an optimum capital structure in line with economic uncertainty. This study makes a worthy contribution to the existing body of knowledge by filling the gap in the evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…The existing literature on culture and finance has also revealed that culture-finance models have endogeneity issues [24]. Endogeneity can occur in three ways in empirical estimations: reversed causality, measuring errors, and omitted factors [65]. In our empirical models, because of omitted variables and measurement mistakes, the regressors can be associated with the error terms.…”
Section: Two-stage Least Square (2sls)mentioning
confidence: 94%
“…The existing literature on culture and finance has also revealed that culture-finance models have endogeneity issues [24]. Endogeneity can occur in three ways in empirical estimations: reversed causality, measuring errors, and omitted factors [65]. In our empirical models, because of omitted variables and measurement mistakes, the regressors can be associated with the error terms.…”
Section: Two-stage Least Square (2sls)mentioning
confidence: 94%
“…The most of research mainly focused on non financial sector of the Pakistan keeping in view their capital structure and the dividend policy (Liaqat, Khan, & Popp, 2021).But very few studies in term of financial sectors focused the capital structure and their dividend policy separately (Liaqat, Khan, & Popp, 2021).However this research using the comparative study of both commercial and the Islamic banks in term of their capital structure and their dividend policy using the most recent data from the tome perod of 15 years from 2006 to 2021.…”
Section: The Novality Of Researchmentioning
confidence: 99%
“…Does borrowing impact dividend payments, with institutions relying more on borrowing paying lower dividends? (Liaqat, Khan, & Popp, 2021). Myers (1984) introduced the of capital structure known as the pecking order theory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some researchers have observed that capital structure is industry specific (Abor, 2007;Abzari et al, 2012;Boquist & Moore, 1984;Bowen et al, 1982;Manjule, 2014;Panda & Nanda, 2020;Rastogi & Narwal, 2014, Schwartz & Aronson, 1967Scott, 1972;Scott & Martin, 1975). Simultaneously, researchers also suggest that the capital structure of industries is dynamic (Liaqat et al, 2021). Industries change their gearing decisions in their endeavour to perpetually balance the cost of capital and rate of return.…”
Section: Introductionmentioning
confidence: 99%